KEABSAHAN DOKUMEN ELEKTRONIK DI DALAM TRANSAKSI BISNIS SECARA ELEKTONIK - Agustina, Sakinah; Dewi Pratiwi, Meirina (Justici, 2024)
ABSTRACT In buying and selling transactions via the internet, it does not rule out the possibility of various unlawful acts occurring, causing losses to other parties. Therefore, it is necessary to think about a solution in the form of legal action that can be taken for an unlawful act that occurred in a buying and selling transaction via the internet. In this way, cases like this can still be resolved legally, so that there is no legal vacuum which could ultimately lead to even greater losses. The type of research that the author uses is normative juridical, namely a method that focuses on research on library data, or secondary data through legal principles and legal comparisons. The authentication or validity of electronic documents and/or their printouts are valid legal evidence which can be seen from Articles 5, 6 and 7 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions.